2009
DOI: 10.1042/cs20080249
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic interval training reduces cardiovascular risk factors more than a multitreatment approach in overweight adolescents

Abstract: The aim of the present study was to compare the effects of a multidisciplinary approach (MTG) and aerobic interval training (AIT) on cardiovascular risk factors in overweight adolescents. A total of 62 overweight and obese adolescents from Trøndelag County in Norway, referred to medical treatment at St Olav's Hospital, Trondheim, Norway, were invited to participate. Of these, 54 adolescents (age, 14.0 +/- 0.3 years) were randomized to either AIT (4 x 4 min intervals at 90% of maximal heart rate, each interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
382
5
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(428 citation statements)
references
References 42 publications
(55 reference statements)
26
382
5
15
Order By: Relevance
“…We believe that thorough evaluation of the endothelial status in large-scale multicenter trials can create a setting enabling the further optimization of training protocols for obese children. One of these training modalities could be aerobic interval training, since data indicate that this type of training is superior in reversing endothelial dysfunction in children (92). Although the participation of children in clinical studies raises several ethical concerns (93), we hope that researchers will continue the fight against childhood obesity.…”
Section: Future Challenges and Perspectivesmentioning
confidence: 99%
“…We believe that thorough evaluation of the endothelial status in large-scale multicenter trials can create a setting enabling the further optimization of training protocols for obese children. One of these training modalities could be aerobic interval training, since data indicate that this type of training is superior in reversing endothelial dysfunction in children (92). Although the participation of children in clinical studies raises several ethical concerns (93), we hope that researchers will continue the fight against childhood obesity.…”
Section: Future Challenges and Perspectivesmentioning
confidence: 99%
“…A significant 4.08kg/m 2 (7.3%) decrease was observed in the BMI of the participants as reported in previous studies with the same principles but longer duration. 43,44 This study shows that FPG reduced by 43.5% (5.28mmol/l) after eight weeks aerobic exercise training which is significantly different from the FPG of the control group (tables 2 & 3). This is in line with earlier studies where six months continuous aerobic exercise training were reported to significantly reduce the mean of FPG as compared to non-exercisers.…”
Section: Discussionmentioning
confidence: 91%
“…The extant literature indicates that, in general, regular physical activity is associated with 15% to 61% reduction in the risk of death from breast or colorectal cancer (Table 1) [83][84][85][86][87]. Of interest, the association between physical activity and cancer-specific mortality is not uniform, which appears to vary according to volume of physical activity and even cancer type.…”
Section: Exercise Therapy Following the Completion Of Adjuvant Therapmentioning
confidence: 96%
“…Of particular interest is highintensity exercise training. Several recent randomized trials have demonstrated that the high-intensity aerobic training (i.e., ‡75% of baseline exercise capacity) causes superior improvements in VO 2peak relative to low-or moderate-intensity exercise training in patients with or at risk of CVD [81][82][83]. However, there is a dearth of data regarding effects of exercise intensity following a cancer diagnosis [79].…”
Section: Exercise Therapy Following the Completion Of Adjuvant Therapmentioning
confidence: 97%